2020
DOI: 10.1111/imm.13174
|View full text |Cite
|
Sign up to set email alerts
|

Kit activates interleukin‐4 receptor and effector signal transducer and activator of transcription 6 independent of its cognate ligand in mouse mast cells

Abstract: Summary Signaling by Kit has been extensively studied in hematopoietic cells and is essential for the survival, proliferation and maintenance of hematopoietic stem and progenitor cells. In addition to the activation of intrinsic signaling pathways, Kit has been shown to interact with lineage‐restricted type I cytokine receptors and produce cross signals, e.g. erythropoietin receptor, interleukin‐7 receptor (IL‐7R), IL‐3R. Based on the earlier studies, we hypothesize that Kit activate other type I cytokine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Both, SCF and IL‐3 activate JAK2, a member of the JAK family, which consists of JAK1‐3 and Tyk2 [6,7]. While SCF stimulation results in downstream activation of STAT5 and STAT6 [7,8], IL‐3 preferentially activates STAT3 and STAT5 [2]. Interestingly, experiments with the IL‐3‐dependent mouse lymphoma cell line DA‐3 demonstrated that also STAT6 can be activated by IL‐3 stimulation [9], but no such data have been shown in primary cells, yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both, SCF and IL‐3 activate JAK2, a member of the JAK family, which consists of JAK1‐3 and Tyk2 [6,7]. While SCF stimulation results in downstream activation of STAT5 and STAT6 [7,8], IL‐3 preferentially activates STAT3 and STAT5 [2]. Interestingly, experiments with the IL‐3‐dependent mouse lymphoma cell line DA‐3 demonstrated that also STAT6 can be activated by IL‐3 stimulation [9], but no such data have been shown in primary cells, yet.…”
Section: Introductionmentioning
confidence: 99%
“…STAT6 has mainly been characterized as a shared downstream target of IL-4 and IL-13 [12,18]. Surprisingly, the Kit (CD117) ligand stem cell factor (SCF) can induce STAT6 activation by utilizing the IL-4R in absence of IL-4 [8]. Downstream the IL-4 receptor, several JAK kinases mediate the signal via chain-specific interactions.…”
Section: Introductionmentioning
confidence: 99%